2021
DOI: 10.1126/sciadv.abe3105
|View full text |Cite
|
Sign up to set email alerts
|

Deformation-induced crystalline-to-amorphous phase transformation in a CrMnFeCoNi high-entropy alloy

Abstract: The Cantor high-entropy alloy (HEA) of CrMnFeCoNi is a solid solution with a face-centered cubic structure. While plastic deformation in this alloy is usually dominated by dislocation slip and deformation twinning, our in situ straining transmission electron microscopy (TEM) experiments reveal a crystalline-to-amorphous phase transformation in an ultrafine-grained Cantor alloy. We find that the crack-tip structural evolution involves a sequence of formation of the crystalline, lamellar, spotted, and amorphous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(44 citation statements)
references
References 44 publications
8
36
0
Order By: Relevance
“…The second nearest-neighbor modified embedded-atom method (2NN MEAM) potential and the parameters developed by Choi et al (2018) are employed to describe the interaction between the atoms, which have been widely used in the MD simulation of mechanical behaviors of CoCrFeNiMn HEA (Fang et al, 2019;Lee et al, 2021;Wang et al, 2021;Zhou et al, 2021). The stacking fault energy of CoCrFeNiMn calculated using these potential parameters is negative, consistent with firstprinciples calculation results (Zhao et al, 2017), which further demonstrates the validity of the potential.…”
Section: Simulation Detailssupporting
confidence: 61%
“…The second nearest-neighbor modified embedded-atom method (2NN MEAM) potential and the parameters developed by Choi et al (2018) are employed to describe the interaction between the atoms, which have been widely used in the MD simulation of mechanical behaviors of CoCrFeNiMn HEA (Fang et al, 2019;Lee et al, 2021;Wang et al, 2021;Zhou et al, 2021). The stacking fault energy of CoCrFeNiMn calculated using these potential parameters is negative, consistent with firstprinciples calculation results (Zhao et al, 2017), which further demonstrates the validity of the potential.…”
Section: Simulation Detailssupporting
confidence: 61%
“…As a near-net or net shape fabrication technology, AM significantly reduces the materials cost by only consuming the required amount of feedstock materials and therefore is ideal for producing components made from expensive materials like many high-entropy alloys (HEAs) [5]. Structural components fabricated by AM can achieve superior properties [6][7][8][9][10], and this is related to the unique microstructures produced by AM [11,12]. For example, a previous research suggested that AM CrMnFeCoNi samples exhibit improved yield strength and ultimate tensile strength compared with as-cast and recrystallized samples fabricated using conventional methods, while maintaining reasonable ductility good enough for most applications [13].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we used a CrMnFeCoNi HEA with an FCC structure, also known as the Cantor alloy, manufactured by LPBF as a sample material to explore the mechanisms of texture evolution determined by local thermal gradients. The Cantor alloy has exceptional mechanical properties at both ambient and cryogenic temperatures [12,30]. A combination of high strength and excellent ductility can be achieved by LPBF [13].…”
Section: Introductionmentioning
confidence: 99%
“…High entropy alloys (HEAs) or multi-component alloys are currently attracting extensive attention from the materials science community due to their excellent properties and potential applications in the aerospace and energy industries. (Gludovatz et al, 2014;Li et al, 2016;Lee et al, 2020;Naeem et al, 2020;Yang et al, 2020;Wang et al, 2021). Particularly, the face-centered-cubic (FCC) HEAs exhibit unique properties such as outstanding ductility, (Otto et al, 2013), high radiation tolerance (Gludovatz et al, 2016) as well as excellent corrosion resistance (Lee et al, 2008).…”
Section: Introductionmentioning
confidence: 99%